SCIENTIFIC EXPEDITIONS TO THE PAMIR AND THE PAMIR REGION IN THE 30S. XX CENTURY. AS INTEGRATED RESEARCH ENTERPRISES: SIGNIFICANCE AND CHARACTERISTICS (Scientific journal of the Fergana State University, 2023)
The article analyzes the features and characteristics of scientific expeditions of the USSR Academy of Sciences in the 30s of the XX century. It is shown that these expeditions were not narrowly focused, but were complex, i.e. they studied numerous problems and solved a whole set of tasks. The research was carried out on the basis of archival materials and works of expedition participants.